2005
DOI: 10.1212/01.wnl.0000184579.23624.6b
|View full text |Cite|
|
Sign up to set email alerts
|

APOE -ε4 predisposes to cognitive dysfunction following uncomplicated carotid endarterectomy

Abstract: Background: Between 9% and 23% of patients undergoing otherwise uncomplicated carotid endarterectomy (CEA) develop subtle cognitive decline 1 month postoperatively. The APOE-ε4 allele has been associated with worse outcome following stroke. Objective: To investigate the ability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 31 publications
2
56
0
3
Order By: Relevance
“…Because the incidence of perioperative stroke is exceedingly rare, investigators are studying subtler forms of neurological injury, such as eCD, to increase the neurological safety of this commonly performed procedure. A number of studies have attempted to elucidate the underlying pathophysiology of this eCD, 3,12,13,18,20,21,31 because it is exhibited by approximately 25% of patients after CEA. This is the first study to evaluate the adequacy of cerebral collateral circulation as a predictor of eCD after CEA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the incidence of perioperative stroke is exceedingly rare, investigators are studying subtler forms of neurological injury, such as eCD, to increase the neurological safety of this commonly performed procedure. A number of studies have attempted to elucidate the underlying pathophysiology of this eCD, 3,12,13,18,20,21,31 because it is exhibited by approximately 25% of patients after CEA. This is the first study to evaluate the adequacy of cerebral collateral circulation as a predictor of eCD after CEA.…”
Section: Discussionmentioning
confidence: 99%
“…All CEA procedures were performed under general anesthesia with routine monitoring as well as continuous electroencephalographic monitoring to detect cerebral ischemia, as previously described. 3,12,13,18,20,21,31 An intraoperative CA shunt was placed in 4 patients with significant electroencephalographic changes consistent with cerebral ischemia, and these patients were subsequently excluded from this study. The remaining 38 patients were included in the statistical analysis.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Risk factors associated with patients that cannot be modified are: the advanced age (Shaw et al, 1987;Diijkstra et al, 1996;Roach et al, 1996;Moller et al, 1998;Abildstrom et al, 2000;Stockton et al, 2000;Ancelin et al, 2001;Newman et al, 2001;Canet et al, 2003;Monk et al, 2008), the educational status (Moller et al, 1998;Abildstrom et al, 2000;Ancelin et al, 2001;Newman et al, 2001;Monk et al, 2008) and the genetic polymorphism (considering apolipoprotein E4) (Abildstrom et al, 2004;Heyer et al, 2005;Lelis et al, 2006). The advanced age is associated with a large number of health problems, many of which can be successfully treated by surgical operations.…”
Section: Non-modifiable Patient Factorsmentioning
confidence: 99%
“…48 Data are inconsistent regarding the role of the apolipoprotein ε4 genotype in perioperative cerebral injury. 2,4,43,87,91,94 Other investigators have examined for a relationship between polymorphisms of genes involved in pathways regulating coagulation, cell adhesion, and inflammation with perioperative cerebral injury. Grocott et al 39 found that the combination of 2 minor alleles of C-reactive protein (CRP; 3′UTR 1846C/T) and interleukin-6 (IL-6; -174G/C) were significantly associated with stroke after cardiac surgery (odds ratio, 3.3; 95% CI, 1.4 to 8.1; P=0.0023).…”
Section: Genetic Predispositionmentioning
confidence: 99%